Deteksi Molekuler Ekson 2 Gen Beta Globin pada Pasien Beta Talasemia Mayor di RSUD DR. Soeroto Ngawi menggunakan Metode Polymerase Chain Reaction- Single Strand Conformation Polimorfism - Yahya Febrianto; Ana Indrayati; Elfahmi . (Fakultas Farmasi Universitas Setia Budi, 2018)
Beta thalassemia is a hereditary blood disorder that caused by genetic disorder ofglobin gene.The condition leads to red blood cell damage so regular blood transfusion isneeded.This study was aimed to determine the presence of mutations in exon 2 gene beta frombeta globin thalassemia patients using PCR-SSCP method. The DNA was isolated from 5samples and amplified using PCR. The amplified product was characterizaed usingelectrophoresis. Region 2 of beta globin was product of primer forward 4 and primer reverse 5with 350 bp of target size. The PCR products of each region then futher analyzed using SSCPmethod. There was indication of mutation in 1,2,3,and 6 samples whereas no mutation insample 5.Based on the results of research can be concluded that PCR-SSCP method can beused to determine the type and location of mutations in exon 2 genes β globin from βthalassemia.